An adaptation-focused evaluation of Canada's first competency-based medical education implementation in radiology. Issue 147 (February 2022) - Chung, Andrew D.; Kwan, Benjamin Y.M.; Wagner, Natalie; Braund, Heather; Hanmore, Tessa; Hall, Andrew Koch; McEwan, Laura; Dalgarno, Nancy; Dagnone, Jeffrey Damon
Highlights: Key Finding: Rapid Evaluation methodology is an effective mechanism for program evaluation in diagnostic radiology, allowing for the identification of areas in which the program curriculum has met, exceeded, or fallen short of intended program objectives. Importance: Following implementation of CBD, program evaluation is necessary to identify the extent to which the intended curriculum was enacted. Abstract: Objectives: Systematic program evaluation of the Queen's University diagnostic radiology residency program following transition to a competency-based medical education (CBME) curriculum. Methods: Rapid Evaluation methodology and the Core Components Framework were utilized to measure CBME implementation. A combination of interviews and focus groups were held with program leaders ( n = 6), faculty ( n = 10), both CBME stream and traditional stream residents ( n = 6), and program staff ( n = 2). Interviews and focus groups were transcribed and analyzed abductively. Study team met with program leaders to review common themes and plan potential adaptations. Results: Strengths of CBME implementation included more frequent and timely feedback as well as the role of the Academic Advisor. However, frontline faculty felt insufficiently supported with regards to the theory and practical implementation of the new curriculum and found assessment tools unintuitive. The circumstances surrounding the curricular implementation also resulted in some negative sentiment. Additional faculty and resident education workshops were identified as areas for improvement as well as changes to assessment tools for increased clarity. Residents overall viewed the changes favorably, with traditional stream residents indicating that they also had a desire for increased feedback. Conclusions: Rapid Evaluation is an effective method for program assessment following curricular change in diagnostic radiology. A departmental champion driving enthusiasm for change from within may be valuable. Adequate resident and faculty education is key to maximize change and smooth the transition. Advances in knowledge: This study provides insights for other radiology training programs transitioning to a CBME framework and provides a structure for programmatic assessment.